Successful aortic valve replacement by overexpanding a SAPIEN transcatheter heart valve for a large aortic annulus (>900 mm2): a case report. Issue 3 (9th February 2023) - Sherwood, Dalton; Nguyen, Peter; Caranasos, Thomas; Vavalle, John
Abstract: Background: There are limited commercial valve sizes available for transcatheter aortic valve implantation (TAVI). This makes it challenging or even prohibitive to perform TAVI on large aortic annuli. Case summary: A 78-year-old male with known low-flow, low-gradient severe aortic stenosis presented with progressive dyspnoea, chest pressure, and decompensated heart failure. Successful off-label TAVI was performed for tricuspid aortic valve stenosis with an aortic annulus of >900 mm 2 . An Edwards S3 29 mm valve was overexpanded with an extra 7 mL of volume at valve deployment. No complications occurred, and only trivial paravalvular leak was seen following implantation. The patient died from a non-cardiovascular cause 8 months following the procedure. Discussion: Patients that require aortic valve replacement with prohibitive surgical risk and have very large aortic valve annuli pose significant technical challenges. This case shows the feasibility of TAVI by overexpanding an Edwards S3 valve.